Agricultural Innovation and Halal Food Security Through Outreach Activities In Balai Balai Panjang - Rahmi Awalina; Wellyalina Wellyalina; Tevina Edwin (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2026)
Balai Panjang Village, Lareh Sago Halaban Subdistrict, Limapuluh Kota Regency, possesses significant potential in the agricultural and socio-economic sectors; however, its utilization remains limited due to structural and managerial constraints, particularly regarding the village’s economic institutions through the Jalur Gemilang Village-Owned Enterprise (BUMNag). This outreach program aims to enhance halal food security through community empowerment and the revitalization of the BUMNag. Activities were carried out through outreach, training in the processing of local agricultural products—such as banana nuggets and cookies—and guidance on agricultural innovations based on appropriate technology. The results of the activities demonstrate an increase in community knowledge regarding the diversification of local food products, the application of appropriate technology, and awareness of the importance of halal food security. Additionally, the community has become more capable of managing local products creatively and competitively. With the revitalization of the BUMNag, it is hoped that this institution can once again serve as a driving force for a self-reliant and sustainable village economy. These findings indicate that community empowerment through participatory approaches and appropriate technology can enhance local capacity in the development of a halal food-based economy.